2004
DOI: 10.1016/j.cogsci.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Generation and evaluation of user tailored responses in multimodal dialogue

Abstract: When people engage in conversation, they tailor their utterances to their conversational partners, whether these partners are other humans or computational systems. This tailoring, or adaptation to the partner takes place in all facets of human language use, and is based on a mental model or a user model of the conversational partner. Such adaptation has been shown to improve listeners' comprehension, their satisfaction with an interactive system, the efficiency with which they execute conversational tasks, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…In a similar study evaluating the output of the MATCH restaurant recommendation system (Walker et al 2004), participants preferred recommendations that were tailored to their own user preferences over those that were tailored to the preferences of some other user. In an overhearer-style user evaluation of the FLIGHTS system-in which the subjects judged the appropriateness of simulated interactions for a hypothetical target user- Demberg and Moore (2006) found that the UMSR approach was preferred over the SR approach; as noted above, the subsequent Winterboer and Moore (2007) study confirmed that the UMSR system also performed better in a task-based evaluation.…”
Section: User Evaluation Of Generated Outputmentioning
confidence: 99%
See 3 more Smart Citations
“…In a similar study evaluating the output of the MATCH restaurant recommendation system (Walker et al 2004), participants preferred recommendations that were tailored to their own user preferences over those that were tailored to the preferences of some other user. In an overhearer-style user evaluation of the FLIGHTS system-in which the subjects judged the appropriateness of simulated interactions for a hypothetical target user- Demberg and Moore (2006) found that the UMSR approach was preferred over the SR approach; as noted above, the subsequent Winterboer and Moore (2007) study confirmed that the UMSR system also performed better in a task-based evaluation.…”
Section: User Evaluation Of Generated Outputmentioning
confidence: 99%
“…AMVF-based user models have been used in a variety of generation systems and domains, including a series of recommender-style systems: GEA (Carenini and Moore 2006), MATCH (Walker et al 2004), and FLIGHTS ). All of these systems generate descriptions and comparisons of options-houses, restaurants, and airline flights, respectively-that are tailored to the user's likes and dislikes.…”
Section: Generating Descriptions Tailored To User Preferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The language generation and dialog management components were developed to capture the dynamic nature of human language production, following earlier approaches involving dynamic dialog constraints (Ericsson 2004), accommodation (Matessa 2000), and adaptive content selection (Walker et al 2004). The focus of the language generation component is on selecting from a set of possible utterances, akin to overgeneration-and-ranking approaches (Varges 2006).…”
Section: Language Generation and Dialog Management Componentsmentioning
confidence: 99%